A Missed Opportunity: The European Union's New Powers over Digital Platforms. (December 2022) - Davies, John; Meunier, Valérie; Calanchi, Gianmarco; Stenimachitis, Angelos
The Digital Markets Act (DMA) in the European Union assumes that all large "core platform service" providers pose similar threats to competition and to fairness and thus imposes identical obligations on all of them. The alternative "New Competition Tool, " that would have allowed the European Commission (EC) to conduct fact-intensive investigations of markets to design bespoke remedies, has been largely abandoned. The approach adopted contradicts the basic principle that competition policy should be concerned with evidence of adverse effects. The proponents of the adopted form of the DMA argue that ex ante action is required to forestall irreversible harm to competition, but that same logic also implies assessing the risk of harm from excessive regulation—and the DMA contains no mechanism to do so. Given the different underlying economics of different kinds of platform services, including the way some support digital ecosystems involving many firms, a different approach is needed. The EC missed the opportunity to introduce a market investigation tool. The rigid and static framework of the DMA seems like the wrong solution, given the economics of digital markets.